Histone methylation codes involved in stemness, multipotency, and senescence in budding tunicates. (January 2015) - Kawamura, Kaz; Kinoshita, Miyuki; Sekida, Satoko; Sunanaga, Takeshi
Graphical abstract: Highlights: Cell longevity and multipotency are unique features in budding tunicates. Histone H3K27 trimethylation (H3K27me3) is a default state of bud and zooid cells. H3K27me3 makes ERK and other transdifferentiation-related genes silent. H3K27me3 and H3K4me3 double-positive signals are involved in cell stemness. The absence of both H3K27me3 and H3K4me3 is a histone code for cell senescence. Summary: We examined the dynamics of nuclear histone H3 trimethylation related to cell differentiation and aging in a budding tunicate, Polyandrocarpa misakiensis . Throughout zooidal life, multipotent epithelial and coelomic cell nuclei showed strong trimethylation signals at H3 lysine27 (H3K27me3), consistent with the results of western blotting. Epidermal H3K27me3 repeatedly appeared in protruding buds and disappeared in senescent adult zooids. The budding-specific cytostatic factor TC14-3 allowed aging epidermal cells to restore H3K27me3 signals and mitochondrial gene activities via mitochondrial transcription factor a, all of which were made ineffective by an H3K27me3 inhibitor. Chromatin immunoprecipitation showed that TC14-3 enhances H3K27me3 of transdifferentiation-related genes and consequently downregulates the expression of these genes. In contrast, trimethylation signals at H3 lysine4 (H3K4me3) appeared transiently in transdifferentiating bud cells and stably lasted in undifferentiated adult cells without affecting H3K27me3. A transdifferentiation-related gene external signal-regulated kinase heavily underwent H3K4me3 in developing buds, which could be reproduced by retinoic acid. These results indicate that in P . misakiensis, TC14-3-driven H3K27 trimethylation is a default state of bud and zooid cells, which serves as the histone code for cell longevity. H3K27me3 and H3K4me3 double-positive signals are involved in cell stemness, and absence of signals is the indication of senescence.